FORMATION OF HUMAN CAPITAL OF AGRICULTURAL ENTERPRISES: FINANCIAL AND RECREATIONAL ASPECTS (World of finance, 2024)
Introduction. The formation of human capital is a critically important aspect of the successful operation of agricultural enterprises. In the conditions of the modern agricultural market, which is characterized by high competition and rapid development of technologies, enterprises are faced with the need to constantly improve the efficiency of their work. Human capital, which includes the knowledge, skills, experience and motivation of employees, becomes a key factor for achieving sustainable growth and innovative development. In this context, investments in education, professional training, development of leadership qualities and creation of favorable working conditions acquire special importance. Effective management of human capital contributes not only to increasing the productivity and competitiveness of agricultural enterprises, but also ensures the sustainable development of rural communities.The purpose of the article is to determine the specifics of the formation of human capital of agricultural enterprises, taking into account recreational and financial aspects.Results. The presented work analyzes and defines the main components of human capital, taking into account the specifics of the agricultural sphere. The definition of the categorical basis of research on the human capital of agricultural enterprises is presented, which in the future makes it possible to more accurately determine the necessary vectors of the development of enterprises in this field and to calculate the influence of financial and recreational aspects. A methodical approach to the formation of human capital of agricultural enterprises was formed, taking into account financial and recreational aspects.Conclusions. The presented research substantiates that the process of human capital formation in agricultural enterprises is a multifaceted process that includes investment in training, creation of favorable working conditions, implementation of innovations and active social responsibility. This contributes not only to increasing the efficiency of enterprises, but also to the development of rural areas as a whole. The presented research results make it possible to form the next steps to improve the human capital of agricultural enterprises by taking into account financial and recreational aspects. The presented research vector makes it possible to focus research efforts on improving human capital precisely at the expense of the presented components, which will further increase the competitiveness of agricultural enterprises.